(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study purposed to find out the effect of career development on employee performance at the Makassar City State Property and Auction Service Office (KPKNL). This study used a quantitative approach. The processed data resulted from the distribution of the instrument in the form of a questionnaire to 54 samples. This study used a saturated sampling technique. The results of the descriptive analysis research showed that the Career Development variable (X) based on indicators of educational background, training, work experience were categorized well with an average score of 59.20% and Employee Performance variable (Y) based on quantity, quality, completion time, cooperation, categorized as good enough with an average score of 57.48%. Based on the results of a simple regression test, it was proved that career development has a positive and significant effect on employee performance at the Makassar City State Property and Auction Service Office (KPKNL). This was concluded, the higher the career development, the employee’s performance could increase.